Illuminating light, cytokinin, and ethylene signalling crosstalk in plant development - Zdarska, Marketa; Dobisová, Tereza; Gelová, Zuzana; Pernisová, Markéta; Dabravolski, Siarhei; Hejátko, Jan (Journal of Experimental Botany, 2015)
Integrating important environmental signals with intrinsic developmental programmes is a crucial adaptive requirement for plant growth, survival, and reproduction. Key environmental cues include changes in several light variables, while important intrinsic (and highly interactive) regulators of many developmental processes include the phytohormones cytokinins (CKs) and ethylene. Here, we discuss the latest discoveries regarding the molecular mechanisms mediating CK/ethylene crosstalk at diverse levels of biosynthetic and metabolic pathways and their complex interactions with light. Furthermore, we summarize evidence indicating that multiple hormonal and light signals are integrated in the multistep phosphorelay (MSP) pathway, a backbone signalling pathway in plants. Inter alia, there are strong overlaps in subcellular localizations and functional similarities in components of these pathways, including receptors and various downstream agents. We highlight recent research demonstrating the importance of CK/ethylene/light crosstalk in selected aspects of plant development, particularly seed germination and early seedling development. The findings clearly demonstrate the crucial integration of plant responses to phytohormones and adaptive responses to environmental cues. Finally, we tentatively identify key future challenges to refine our understanding of the molecular mechanisms mediating crosstalk between light and hormonal signals, and their integration during plant life cycles.
Keywords: Cytokinins; ethyleny; Ethylenes; Light; regulátory růstu rostlin; světlo; vývoj rostlin; Plant Development; signální transdukce; Plant Growth Regulators; cytokininy; Signal Transduction